An Account of Egypt - Herodotus, 481? BCE-421? BCE; Macaulay, G. C. (George Campbell), 1852-1915 (Salt Lake City, UT : Project Gutenberg, 2006)
"An Account of Egypt" by Herodotus is a historical account likely written in the early part of the fifth century BC. It explores the history, culture, and geography of Egypt, presenting various customs, rituals, and significant events in the context of both Egyptian and Greek perspectives. The book delves into the interactions between Greeks and Egyptians, the marvels of Egyptian civilization, and the significance of the Nile River in shaping the landscape and lives of the Egyptians. The beginning of "An Account of Egypt" sets the stage for an in-depth exploration of the region. It recounts how Cambyses, the son of Cyrus, marched against Egypt and introduces the narrative about Psammetichos, an early king who sought to determine the origins of humanity through an intriguing experiment with two children raised in isolation. Herodotus conveys information gathered from various priests during his travels, emphasizing the cultural complexities of Egypt. He highlights the division of the year and showcases the unique customs of the Egyptians, including their religious practices and notable legends surrounding animals like the crocodile and the sacred phoenix. This opening reveals Herodotus's approach as both an observer and a storyteller, hinting at the rich and multifaceted history that unfolds throughout the text. (This is an automatically generated summary.)
Release date is 2006-02-26
Produced by John Bickers; Dagny; David Widger
Keywords: Egypt -- History -- To 332 B.C.